A Study of Colonial Confrontation in The Things Fall Apart - Md Eaqub Ali (International Journal of Applied Educational Research (IJAER), 2024)
This research paper critically examines the portrayal of colonial confrontation in Chinua Achebe’s "Things Fall Apart," highlighting the themes of suppression and oppression. It argues that Achebe adeptly reconstructs the historical and political context of the Igbo people's recent past, illustrating their suppression and oppression by European colonizers. Furthermore, the paper explores how Achebe portrays Igbo community life and demonstrates how the arrival of white missionaries and colonial administrators gradually undermined traditional Igbo values. This erosion occurred initially through religious conversions and later through the imposition of colonial political structures, ultimately leading to the dismantling of traditional Igbo society. Thus, the novel addresses various forms of suppression—social, political, religious, cultural, economic, and educational—imposed on the Igbo tribe by the British colonial administration.